Forecasting ECB monetary policy: accuracy is (still) a matter of geography - Helge Berger; Michael Ehrmann; Marcel Fratzscher (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2006)
Monetary policy in the euro area is conducted within a multi-country, multi-cultural, and multi-lingual context involving multiple central banking traditions. How does this heterogeneity affect the ability of economic agents to understand and to anticipate monetary policy by the ECB? Using a database of surveys of professional ECB policy forecasters in 24 countries, we find remarkable differences in forecast accuracy, and show that they are partly related to geography and clustering around informational hubs, as well as to country-specific economic conditions and traditions of independent central banking in the past. In large part this heterogeneity can be traced to differences in forecasting models. While some systematic differences between analysts have been transitional and are indicative of learning, others are more persistent.
Keywords: E52; E58; G14; 330; monetary policy; ECB; forecast; geography; history; heterogeneity; Taylor rule; learning; transmission; survey data; communication; Geldpolitik; Prognose; Kritik; Taylor-Regel; Transmissionsmechanismus; Regionale Disparität; EU-Staaten